Chemical constituent with cytotoxicity from Sterculia diversifolia. Issue 9 (2nd September 2021) - Rabbi, Fazle; Zada, Amir; Adhikari, Achyut; Nisar, Amna; Khalil, Saifullah Khan
Abstract: One new coumarin (stercularin), along with eleven known compounds, was isolated for the first time from ethyl acetate fraction of Sterculia diversifolia. The structures of isolated compounds were characterized by spectroscopic techniques such as EIMS, 1 H-NMR and 13 C-NMR. Compound 1 showed significant cytotoxicity by brine shrimp lethality assay (LD50 : 8.00 μg/ml) and PC-3 cell lines protocol (IC50 : 3.92 ± 0.20 μg/ml), respectively. Graphical abstract: UF0001